Long-Term Change of Demersal Fish Assemblages on the Inshore Agulhas Bank Between 1904 and 2015 - Currie, Jock C.; Atkinson, Lara J.; Sink, Kerry J.; Attwood, Colin G. (Frontiers in Marine Science, 2020)
Without baseline data from near pristine assemblages, measures of ecosystem change may be significantly underestimated. A unique historical dataset provided an opportunity to investigate long-term change in demersal fish assemblages of South Africa's inshore trawl grounds. Three sites surveyed over a period from 1903 to 1904 were re-surveyed in 2015 using replicated historical gear and methods. Catch composition was contrasted between historical and modern periods using unconstrained ordination, permutational multivariate analysis of variance, permutational tests of the homogeneity of multivariate group dispersions and similarity percentage analyses. After 111 years, the re-survey revealed a drastically transformed demersal assemblage, with the period effect explaining nearly half of the variance among samples. Historical catches were dominated by kob (Argyrosomus spp.), panga (Pterogymnus laniarius) and east coast sole (Austroglossus pectoralis), jointly contributing 70-84% of the catch. The same taxa made up a minor component (1.5-5.5%) of modern assemblages. Instead, the re-survey catches consisted predominantly of gurnards (Chelidonichthys spp.), Cape horse mackerel (Trachurus capensis), spiny dogfish (Squalus spp.), shallow-water hake (Merluccius capensis) and white sea catfish (Galeichthys feliceps), with their summed contribution rising to 85% from the historical 3%. These results suggest that a century of trawling may have altered benthic habitats, indirectly contributing to changes in the fish community. Historical assemblages included a substantial proportion of taxa that associate with reef habitats, whereas the re-survey assemblages were characterised by species that inhabit unconsolidated sediments or both reef and non-reef habitats. The unique historical context and data, comparable gear and methods and long temporal period revealed striking baseline changes that may be overlooked in most fisheries. Reconstructing this important historical context improves our ability to assess, interpret and manage changing marine ecosystems.